Retroperitoneal haemorrhage caused by a renal angiomyolipoma - Ünlü, C (BMJ Group, 2006)
Renal angiomyolipoma (AML) is a benign renal tumour and is nowadays considered a relatively common lesion. When an AML increases in size or becomes symptomatic, embolisation via the renal artery should then be considered, because rupture is an important complication and interventional therapies are required to stop bleeding. We present a 21 year old woman who was seen at the emergency department following a low velocity trauma. After a period of 9 weeks, clinical examination and radiological examination revealed a haemorrhage from a renal AML, which was treated by selective embolisation. A discussion of the relevant literature is also presented.